Ocean acidification adversely influences metabolism, extracellular pH and calcification of an economically important marine bivalve, Tegillarca granosa. (April 2017) - Zhao, Xinguo; Shi, Wei; Han, Yu; Liu, Saixi; Guo, Cheng; Fu, Wandong; Chai, Xueliang; Liu, Guangxu
Abstract: Oceanic uptake of CO2 from the atmosphere has significantly reduced surface seawater pH and altered the carbonate chemistry within, leading to global Ocean Acidification (OA). The blood clam, Tegillarca granosa, is an economically and ecologically significant marine bivalve that is widely distributed along the coastal and estuarine areas of Asia. To investigate the physiological responses to OA, blood clams were exposed to ambient and three reduced seawater pH levels (8.1, 7.8, 7.6 and 7.4) for 40 days, respectively. Results obtained suggest that OA suppresses the feeding activity and aerobic metabolism, but elevates proteins catabolism of blood clams. OA also causes extracellular acidosis and decreases haemolymph Ca 2+ concentration. In addition, our data also suggest that OA impairs the calcification process and inner shell surface integrity. Overall, OA adversely influences metabolism, acid-base status and calcification of blood clams, subsequently leading to a decrease in the fitness of this marine bivalve species. Graphical abstract: Highlights: Physiological effects of Ocean Acidification (OA) on blood clams were investigated. OA suppresses the feeding activity and aerobic metabolism of blood clams. OA causes high proteins catabolism of blood clams. OA leads to extracellular acidosis and reduces haemolymph Ca 2+ level of blood clams. OA impairs the calcification process and corrodes inner shell surfaces of blood clams.